Update of syncytiotrophoblast derived extracellular vesicles in normal pregnancy and preeclampsia. (February 2017) - Tannetta, Dionne; Masliukaite, Ieva; Vatish, Manu; Redman, Christopher; Sargent, Ian
Highlights: The syncytiotrophoblast releases extracellular vesicles (STBEV) and nuclear aggregates (SNA) in normal pregnancy and preeclampsia (PE). STBEV and SNA carry a complex cargo of proteins, glycans, lipids and RNAs that may reflect the functional state of the syncytiotrophoblast. STBEV and SNA may be involved in modification of maternal cell function during normal pregnancy and pathological changes associated with PE. Analysis of circulating STBEV cargo could reveal novel biomarkers of placental stress that can occur in PE. Abstract: The release of extracellular vesicles (EV) by the syncytiotrophoblast (STB) may be an important mechanism by which the placenta signals to the mother. STB derived EV (STBEV) are comprised predominantly of exosomes (50–150 nm) and microvesicles (100–1000 nm) that contain bioactive mediators such as proteins, nucleic acids and lipids. They, along with larger syncytial nuclear aggregates are released by the STB into the maternal circulation throughout gestation in normal pregnancy where they appear to have an immunoregulatory role, inhibiting T cell and NK cell responses. In pre-eclampsia (PE) STBEV are released in significantly increased numbers and have pro-inflammatory, anti-angiogenic and procoagulant activity, implicating them in the maternal systemic inflammation, endothelial dysfunction and activation of the clotting system which typifies the disorder. Research has focused on understanding the biological significance of STBEV by measuring their size and repertoire of molecules carried and how they differ in normal pregnancy and PE, using techniques such as Nanoparticle Tracking Analysis, flow cytometry and mass spectrometry. We have also found alterations in STBEV surface glycans associated with PE. The goal is to better understand the role STBEV play in normal pregnancy and PE and whether they are potential biomarkers of placental pathology and therapeutic targets in PE.